Using Fluency Training to Enhance the Conjugation of Spanish Verbs - (:unkn) unknown (My University, 2014)
This study explored whether a treatment package that included fluency training, Precision Teaching, multiple discrimination, matching to sample, and cumulative practice procedures could teach students to correctly translate noun clauses such as "April cried" from English to Spanish and correctly conjugate the Spanish verb in the clauses even though the conjugation had not been directly trained. The verbs were in the past tense (preterit) and drawn from three classes such that verb inflection in Spanish was identical for verbs within a class and with only a few exceptions different for verbs from different classes. Three students who could not correctly inflect these verbs used special software for 20 min daily on their own and came to the laboratory twice weekly to verify their training. Multiple discrimination procedures taught translation from English to Spanish of nouns and verbs as well as the conjugation of two members of each verb class. Matching to sample procedures established the three verb classes. The major issue was transfer: When participants translated, could they conjugate the Spanish verbs whose conjugations had not been directly trained? Three transfer tests were constructed. Each test contained English clauses that when translated required Spanish verbs from one class. An additional test included clauses from all the tests. These training procedures and battery of tests were arranged to form, at the level of each participant, a multiple probe design replicated across verb classes. The treatment package was effective for one participant who came to fluently translate and conjugate at rates comparable to those of an experience bilingual speaker. This outcome was not replicated with the other two participants. These failures to replicate were discussed and suggestions for future research were presented.
Keywords: ABA; Applied Behavior Analysis; Fluency; Language; Spanish